Factors affecting distance to the nearest physician in Canada: Changes from 1993-1999. - Amankwah, Nana Akwasi. (University of Ottawa (Canada), 2002)
Ability to pay for physician services is not a barrier to service in Canada, but travel distance may restrict some people's access, especially in rural areas. This thesis examines the distance to the nearest physician from a representative point within each of Canada's census enumeration areas in 1999, and the nature and extent of changes in these distances since 1993. The study is based on the 1999 postal codes of the 56,775 physicians in the Canadian Medical Association registry. Distance to the nearest physician has changed little since 1993; 87% of the population still live less than 5 km from the nearest physician. Distance to the nearest physician was greater in rural areas and small towns, in less urbanized provinces/territories, at higher latitudes, and in less urbanized low-income areas. Physicians-to-population ratios also decreased by 6% from 1993 to 1999.
Keywords: Health Sciences, Public Health.